Protein tyrosine phosphatase 1B gene polymorphisms and essential hypertension: a case-control study in Chinese population - Gu, P; Jiang, W; Du, H; Shao, J; Lu, B; Wang, J; Zou, D (Journal of endocrinological investigation, 2010)
Protein tyrosine phosphatase (PTP)- 1B, encoded by the PTPN1 gene, negatively regulates insulin signaling by dephosphorylating the phosphotyrosine residues of the insulin receptor kinase activation segment. Several rare single nucleotide polymorphisms (SNP) have been linked to diseases accompanying insulin resistance such as Type 2 diabetes, obesity, and dyslipidemia in different populations. To investigate whether PTP-1B SNP are associated with hypertension and hypertension-related metabolic traits in Chinese subjects. A total of 239 Chinese patients with hypertension and 141 non-hypertensive subjects were screened. The genotypes of PTP-1B gene polymorphisms were determined by PCR-restriction fragment length polymorphism methods. The case-control study showed associations between the frequencies of T allelic g54281 T>A and A allele of I5/37C>A and hypertension (p<0.0001, p=0.0371, respectively). In addition, significant associations were observed between the IVS6+G82A polymorphism and waist circumference, total cholesterol, and LDL-cholesterol levels in hypertensive patients (p=0.0005 approximately 0.0260). And g54281 T allele was associated with higher plasma triglyceride (p=0.0390) and LDL-cholesterol concentration (p=0.0141), while g58585 T>C was associated with body mass index (BMI) (p=0.0308), waist circumference (p=0.0216), and homeostasis model assessment of insulin resistance (p=0.047). Multivariate logistic regression analysis showed that T allele carriers of g54281T>A and A allele carriers of I5/37C>A had higher risks of hypertension independent of age, gender, BMI, glucose levels, and lipids profiles [odds ratio (OR): 1.79, 95% confidence interval (CI): 1.09- 2.96, p=0.02; OR: 1.66, 95% CI: 1.13-2.44, p=0.01, respectively]. PTP-1B polymorphisms contribute to pathogenesis of hypertension in Chinese subjects and PTP-1B SNP may be involved in the development of several features including dyslipidemia and obesity in hypertensive subjects.